The effect of the directed educational imagination strategy on the expressive performance of fifth grade science students (Journal of the College of Basic Education, 2022)
The current research aims to investigate the effect of educational guided imagery in expressive performance of fifth-grade students the scientific strategy.To achieve the aim of the research scholar null hypothesis the following situation: there is no difference statistically significant between the average scores of the experimental group students who are studying the expression strategy for educational guided imagery, and the average score of the control group students who are studying the same material in the traditional manner, a researcher Qsidia chose junior Gamal Abdel Nasser for Boys, which includes two divisions of the fifth grade science, randomly selected Division (a) to represent the experimental group, while represented Division (b) the control group, reached the research sample (50 students) by (25) students the experimental group and 25 students of the control group, a researcher between them parity in the variables (chronological age, calculated in months, and academic achievement for parents, and degrees of Arabic language material), the researcher developed a questionnaire ensured sixteen topic expression, presented to a group of experts, to choose six subjects including, a researcher at the present research adopted the umpires correct ready, It umpires correct Hashemi to correct the writings of the two groups of students search experimental and control, to be a tool to measure their performance expressionist. Using samples t-test, the study yielded the following result:Outweigh the experimental group students who are studying the expression educational strategy guided imagery to the control group students who are studying in the traditional manner of expression, and statistical terms (0.05). In light of the search result researcher concluded that the strategy of the educational effectiveness of guided imagery in raising the level of expressive performance of fifth-grade students and scientific researcher recommended the need for knowledge of the Arabic language teachers.He suggested a number of studies to complement the current study on students and other stages of learning